1981
DOI: 10.1159/000232816
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine Production by PHA-Stimulated Human Lymphocytes is Enhanced by Interferon

Abstract: Human interferon (IFN) was examined for its capacity to modify the phytohaemagglutinin (PHA)-triggered release of mitogenic factors (MF) from human lymphocytes in vitro. It was observed that the presence of partially purified leukocyte IFN (IFN-α) during the PHA pulsing of the lymphocytes increased their subsequent release of factors which were mitogenic for fractionated T cells. A similar effect was also observed when lymphocytes were exposed to IFN-α prior to PHA pulsing. The possibility that substances in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Perhaps enhanced Ly-6 antigen expression mediated by IFN amplifies the capacity to T cells to respond to additional stimuli. Interestingly, earlier studies have shown that pretreatment of human T cells with IFN augments their subsequent release of lymphokines upon exposure to phytohemagglutinin [25].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps enhanced Ly-6 antigen expression mediated by IFN amplifies the capacity to T cells to respond to additional stimuli. Interestingly, earlier studies have shown that pretreatment of human T cells with IFN augments their subsequent release of lymphokines upon exposure to phytohemagglutinin [25].…”
Section: Discussionmentioning
confidence: 99%
“…(31,3 2) It can augment the cytotoxic activity of NK cells (33,34) and the production of certain cytokines. (35)(36)(37)(38)(39) However, in spite of extensive studies, the mechanism s by which the immunostimulatory actions of IFN-a occur are not fully understood.…”
Section: Introduction F Ibr O M Y Amentioning
confidence: 99%